2013
DOI: 10.1002/2013jd020294
|View full text |Cite
|
Sign up to set email alerts
|

The influence of major sudden stratospheric warming and elevated stratopause events on the effects of energetic particle precipitation in WACCM

Abstract: [1] We investigate the influence of major sudden stratospheric warming (SSW) and elevated stratopause (ES) events in the Northern Hemisphere winter on the transport of NO x produced by energetic particle precipitation (EPP) from the mesosphere-lower thermosphere to the stratosphere using the Whole Atmosphere Community Climate Model (WACCM). Increases in NO x following a major SSW and/or ES event are in excess of 100% compared to winters when no major SSW or ES event occurred. The increase in NO x is attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 38 publications
(56 reference statements)
5
63
0
Order By: Relevance
“…Moreover, this figure shows that the tongue of dry air observed by SMR extended at least 5 km lower in the stratosphere in 2013 than in 2009. These results are perfectly consistent with the study carried out by Holt et al (2013), which showed that the earlier a SSW event occurs in the winter season, and the stronger is the descent following the event.…”
Section: Middle Atmospheric Dynamical Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, this figure shows that the tongue of dry air observed by SMR extended at least 5 km lower in the stratosphere in 2013 than in 2009. These results are perfectly consistent with the study carried out by Holt et al (2013), which showed that the earlier a SSW event occurs in the winter season, and the stronger is the descent following the event.…”
Section: Middle Atmospheric Dynamical Activitysupporting
confidence: 93%
“…The differences between these two winters can be explained by the earlier onset of the dynamical event in 2013 compared to 2009. Holt et al (2013) indeed showed that the EPP indirect effect is larger for earlier central warming dates for two main reasons: the earlier an event occurs in the winter season, the stronger is the following descent, and the longer the EPP-NO x can be transported down before the final warming occurs. This highlights the importance of the dynamics for the EPP IE.…”
Section: K Pérot Et Al: 2013 Arctic No In Odin/smr Data 3 Summary Amentioning
confidence: 93%
“…Interannual variations of the EPP-NO y seasonal dependence, driven by variations of chemical losses and transport patterns, are not considered in the standard mode of the UBC model. Optionally, episodes of accelerated descent associated with elevated stratopause (ES) events in Arctic winters can be considered by means of a dedicated parameterization, taking into account the dependence of the EPP-NO y amounts and fluxes on the event timing (Holt et al, 2013). Although its application is recommended in principle, we note that it requires the implementation of the UBC model into the climate model system since ES events cannot be predicted in free-running model simulations.…”
Section: The Epp Indirect Effect: Odd Nitrogen Upper-boundary Conditionmentioning
confidence: 99%
“…Periods of strong atmospheric descent are known to coincide with the timing of sudden stratospheric warmings (SSWs; e.g. Manney et al, 2003Manney et al, , 2009Jackman et al, 2009;Siskind et al, 2010;Holt et al, 2013). Elevated VMRs of carbon monoxide (CO) and NO x have been observed to linger in the middle atmosphere when there is an exceptionally strong polar vortex after a strong SSW, helping to confine descending air at the pole (Randall et al, 2006).…”
Section: Introductionmentioning
confidence: 99%